Knowledge management in higher education a case study in Malaysia - Sharimllah Devi Ramachandran (Penerbit Universiti Teknikal Malaysia Melaka, 2010)
This book provides a clear coverage of Knowledge Management processes and its measurement: Knowledge Management Performance Outcomes. Challenges and needs for KM in higher education are outlined before closing with concise, practical recommendations that will help academics and administrators improve KM programmes in their institutions.